Mejora de la distribución en planta del proceso de fabricación de tintas para el proceso de elaboración de empaques para alimentos y cuidado personal (2021)
The interrelation of responsibilities to reach the same end, at the moment of applying the distributions to find possible failures and filter them, until finding a solution to the problem, with the tools of continuous improvement plant distribution we will show the reduction of time and displacements in the production process, storage of raw material to the final product. Its focus is to verify, check and ratify if the proposal is what the company really needs and why it needs it. To do so, it will only be limited to observation, where the plant is distinguished and the points where the problems are concentrated in which the requirement of the time-taking is reflected are detailed, by means of the plant distribution tool.